Does visual redundancy inhibit older persons' information processing in learning?. Issue 9 (1st September 2016) - Zheng, Robert; Smith, Derek; Luptak, Marilyn; Hill, Robert D.; Hill, Justin; Rupper, Randall
ABSTRACT: This study investigated the redundancy effect on older and younger persons' cognitive performance in a caregiver video training. Participants ( N  = 92) were recruited from one research-intensive university and three senior centers in a midsize city in the western United States. The mixed within- and between-subjects design was used. Participants watched the caregiving video with caption followed by a video without caption or vice versa depending on the condition. The results showed that older persons benefited from the redundancy learning whereas younger persons suffered from the redundancy learning. Implications of the findings are discussed with suggestions for future research.